Characterization of chain conformations in perfluorosulfonic acid membranes using electron energy loss spectroscopy. Issue 3 (8th December 2014) - Wang, Chen; Duscher, Gerd; Paddison, Stephen J.
Abstract : The side chain effects on the PTFE backbone conformation in the family of perfluorosulfonic acid ionomers were first investigated with electron energy-loss spectroscopy and first principles calculations. Abstract : Chain conformations of the perfluorosulfonic acid (PFSA) ionomers: Nafion™ and Aquivion® were investigated with electron energy-loss spectroscopy (EELS) on a 200 kV transmission electron microscope (TEM) equipped with a monochromator. The results were compared with polytetrafluoroethylene (PTFE) to evaluate the effect of the pendant perfluoroether side chains of the ionomers on the structure of the PTFE backbone. Several unique spectroscopic features corresponding to conformational changes were identified in the low-loss region and the fine structures of the carbon K-edge. Results obtained from high-level density function theory (DFT) based electronic structure calculations confirmed the conformational dependence of the EEL spectra of the PFSA ionomers. Comparison with the spectra obtained from the experiments revealed the correlation between the specific side chain chemistry and backbone conformation. This spectroscopic information will allow us to further explore the morphological properties of these materials when combining with additional imaging techniques.